1982
DOI: 10.2307/1219680
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Multivariate Methods for the Detection of Hybridization

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. International Association for Plant Taxonomy (IAPT)is collaborating with JSTOR to digitize, preserve and extend access to Taxon. SummaryPrincipal component analysis (PCA), Wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
3

Year Published

1983
1983
2007
2007

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 22 publications
1
33
0
3
Order By: Relevance
“…The method of major components applied in the study of plan natural hybridization (Adams 1982;Wilson 1992, and others) was used for the identification of spontaneous hybrids and the analysis of their variation.…”
Section: Methodsmentioning
confidence: 99%
“…The method of major components applied in the study of plan natural hybridization (Adams 1982;Wilson 1992, and others) was used for the identification of spontaneous hybrids and the analysis of their variation.…”
Section: Methodsmentioning
confidence: 99%
“…the F I weighted Wells' distance diagram (Adams 1982). Although useful results have been obtained with this method, e.g.…”
Section: Weighting Ofanalysis Methodsmentioning
confidence: 99%
“…Principal components, hybrid indices, and similar methods may be useful in analyzing introgression and swarm structure after one has already demonstrated that hybridization is involved to begin with. Unfortunately, methodological papers on this topic have not made it clear that the methods for showing introgression or swarm structure are not acceptable for showing hybridity itself, and that before even trying to show introgression or swarm structure it is necessary to first show hybridity (e.g., Anderson, 1949;Hatheway, 1962;Namkoong, 1966;Wells, 1980;Pimentel, 1981;Adams, 1982;Brockmann, 1987).…”
Section: Character Count Proceduresmentioning
confidence: 99%